OPTIMASI PROSES EKSTRAKSI KITIN MENJADI KITOSAN DARI LIMBAH KULIT ULAT HONGKONG ( TENEBRIO MOLITOR ) - Asih Budiutami; Nurhua Kumala Sari; Slamet Priyanto (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2012)
Chitosan has a lot of benefits such as antifungal, antibacterial, coatings, absorbing water and fat.Most of research to process chitosan use a waste from crustaceans such as shrimp, small crab skins, leather and other crabs. But in reality, there are many other types of arthopoda that contain chitin, for example is the class of Insecta as Tenebrio Molitor (meal worm). Meal worm contain the chitin in the skin. Meal worm change of skin as much as 15 times before it finally turns into a cocoon. it is the waste in meal worm cultivation and still have rich in chitin. To extract the chitin into chitosan consists of three stages namely deprotenisasi, demineralization and deacetylation. Product of in this research is if with increase of consentration NaOH and increase of operation temperature so protein contain will be decrease, mineral contain so much the decrease, and deacetylation of degree be increase. Optimum condition of deproteinisation process at 3% w/v concentration of NaOH and temperature at 90 oC with protein contain 4,25%. Optimum condition of demineralization process at 2,5 N concentration of HCl with Ca contain 0,76% and Mg contain 2,44 mg/100gr. Optimum condition of deacetylation process at 5% w/v concentration of NaOH and temperature at 100oC with deacetylation of degree is 61,2% and product of rendemen is 33,1%.